2014
DOI: 10.1186/preaccept-1467335606136283
|View full text |Cite
|
Sign up to set email alerts
|

A novel small-molecule MRCK inhibitor blocks cancer cell invasion

Abstract: Background: The myotonic dystrophy kinase-related CDC42-binding kinases MRCKα and MRCKβ regulate actin-myosin contractility and have been implicated in cancer metastasis. Along with the related ROCK1 and ROCK2 kinases, the MRCK proteins initiate signalling events that lead to contractile force generation which powers cancer cell motility and invasion. A potential strategy for cancer therapy is to reduce metastasis by blocking MRCK activity, either alone or in combination with ROCK inhibition. However, to date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 23 publications
6
30
0
Order By: Relevance
“…However, there is another group of AGC kinases in which the polar residue linked to the water network is instead located at a third cavity position (104 in PKA numbering) (Figure 5f). The x-ray structure of MRCK, a representative member of this group, shows that this leads to a more AurA-like hexagonal water network (Figure 5f) 47 . Apparently there are several classes of water network in different kinases, distinguished by the position of the polar amino acid that participates in the hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is another group of AGC kinases in which the polar residue linked to the water network is instead located at a third cavity position (104 in PKA numbering) (Figure 5f). The x-ray structure of MRCK, a representative member of this group, shows that this leads to a more AurA-like hexagonal water network (Figure 5f) 47 . Apparently there are several classes of water network in different kinases, distinguished by the position of the polar amino acid that participates in the hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the ability of human SCC12 squamous cell carcinoma cells to invade a 3D collagen matrix was strongly inhibited by 2-μM BDP5290 but not by the identical concentration of Y27632, despite equivalent inhibition of MLC phosphorylation [120].…”
Section: Candidate Migrastatic Drugsmentioning
confidence: 92%
“…Nevertheless, it encouraged the development of second-generation ROCK and/or MRCK inhibitors such as RKI-18, BDP5290 or DJ4, which show substantially better specificity. Although these inhibitors are widely used in experimental conditions, no in vivo data are yet available for RKI-18 [119], BDP5290 [120] or DJ4 [122]. However, DJ4 was found to inhibit the invasiveness of human breast carcinoma MDA-MB-231 cells [122].…”
Section: Candidate Migrastatic Drugsmentioning
confidence: 99%
“…This mode of invasion is characterized by an elongated cell body, actin-rich protrusions, and actinmyosin contractility at the rear of the migrating cells. Unbekandt and colleagues have recently demonstrated that MRCK can drive cancer cell migration, a process that can be inhibited by specific small-molecule inhibitors (15)(16)(17). Because CDC42 activity is upregulated in glioma (18,19) and may drive the mesenchymal mode of migration employed by infiltrating glioma cells, we investigated a potential role for MRCK-driven GBM cell invasion in the pathogenesis of GBM.…”
Section: Introductionmentioning
confidence: 99%